Approximation of Functions of Many Variables from the Classes B_p,θ^Ω (ℝ^d) By Entire Functions of Exponential Type - Myronyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We obtain the decomposition representation of the norm of functions of many variables from the spaces B_p,θ^Ω (ℝ^d) and establish the exact order estimates for the approximations of functions from the unit balls of these spaces by entire functions of exponential type in the space L_q (ℝ^d).